The therapeutic effects of curcumin on polycystic ovary syndrome by upregulating PPAR-γ expression and reducing oxidative stress in a rat model - Zhang, Wei; Peng, Cong; Xu, Lei; Zhao, Yutai; Huang, Chaolin; Lu, Ling (Frontiers in Endocrinology, 2024)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine and metabolic disorder that impacts 8-13% of women in their reproductive years. However, the drugs commonly used to treat PCOS are often prescribed off-label and may carry potential side effects. This study aimed to investigate the therapeutic effects of curcumin in a PCOS rat model.A PCOS rat model was established through daily subcutaneous injection of 60 mg/kg body weight of dehydroepiandrosterone (DHEA) for 21 days. The PCOS rats received a daily intragastric dose of 50 mg/kg body weight of curcumin for another 21 days.Ovarian morphological changes, estrous cycle changes, and hormone level changes were measured to evaluate the therapeutic effectiveness of curcumin in PCOS rats.Oxidative stress markers in the ovaries were analyzed to explore the mechanisms of curcumin in PCOS rats.This study demonstrated that curcumin alleviated insulin resistance and significantly reduced serum levels of estradiol (p = 0.02), luteinizing hormone (p = 0.009), testosterone (p = 0.003), and the LH/FSH ratio (p = 0.008) in PCOS rats.Curcumin also restored normal ovarian morphology and the estrous cycle in these rats.Furthermore, curcumin treatment significantly decreased levels of oxidative stress markers, including malondialdehyde (p = 0.004) and reactive oxygen species (p = 0.005), while increasing antioxidant levels such as superoxide dismutase (p = 0.04), glutathione peroxidase (p = 0.002), and glutathione (p = 0.02) in ovarian tissues.Additionally, curcumin significantly upregulated PPAR-γ in the ovarian tissues of PCOS rats.This study demonstrates that curcumin effectively restores ovarian morphology, hormone levels, and estrous cycles in PCOS rats. These effects may be linked to its ability to reduce oxidative stress in ovaries via the upregulation of PPAR-γ. Curcumin shows promise as a potential drug for the treatment of PCOS.